2018
DOI: 10.1073/pnas.1806878115
|View full text |Cite
|
Sign up to set email alerts
|

Lithium metal stripping beneath the solid electrolyte interphase

Abstract: Lithium stripping is a crucial process coupled with lithium deposition during the cycling of Li metal batteries. Lithium deposition has been widely studied, whereas stripping as a subsurface process has rarely been investigated. Here we reveal the fundamental mechanism of stripping on lithium by visualizing the interface between stripped lithium and the solid electrolyte interphase (SEI). We observed nanovoids formed between lithium and the SEI layer after stripping, which are attributed to the accumulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
182
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(192 citation statements)
references
References 34 publications
4
182
0
Order By: Relevance
“…The inhomogeneous dissolution on the entire surface of Li could be related to the crystallographic orientations of different Li grains. Some crystallographic orientations could be more susceptible to Li dissolution than others 25 . The end of the cycling curve (Figure S3 ) also shows significant voltage fluctuations, indicating the consumption of Li electrode and the consequent loss of contact.…”
Section: Resultsmentioning
confidence: 99%
“…The inhomogeneous dissolution on the entire surface of Li could be related to the crystallographic orientations of different Li grains. Some crystallographic orientations could be more susceptible to Li dissolution than others 25 . The end of the cycling curve (Figure S3 ) also shows significant voltage fluctuations, indicating the consumption of Li electrode and the consequent loss of contact.…”
Section: Resultsmentioning
confidence: 99%
“…3i-k). 31 During the repeated platingstripping process, such densely packed and smooth Li morphology found on the LiNO 3 -treated Li-metal surface significantly suppressed the unwanted interfacial reaction between the electrolyte and Li-metal surface and exhibited the least amount of Li loss as a dead layer compared to the bare Li-metal ( Fig. 4a-f).…”
Section: Characterization Of Li-deposit Morphologiesmentioning
confidence: 93%
“…found that under high‐rate electrochemical Li dissolution, the vigorous growth of voids causes a local collapse of SEI layer. [ 105 ] The breakdown sites react much faster than other areas, leading to pit growth. The total area coverage of pits increases as the current density increases.…”
Section: Factors Affecting the Properties Of Solid Electrolyte Interpmentioning
confidence: 99%